Constraining hadronization mechanisms with Λc+/D0 production ratios in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Physics letters, 2023)
The production of prompt Λc+ baryons at midrapidity (|y|<0.5) was measured in central (0-10%) and mid-central (30-50%) Pb-Pb collisions at the center-of-mass energy per nucleon-nucleon pair sNN=5.02 TeV with the ALICE detector. The results are more precise, more differential in centrality, and reach much lower transverse momentum (pT=1 GeV/c) with respect to previous measurements performed by the ALICE, STAR, and CMS Collaborations in nucleus-nucleus collisions, allowing for an extrapolation down to pT=0. The pT-differential Λc+/D0 ratio is enhanced with respect to the pp measurement for 4<pT<8 GeV/c by 3.7 standard deviations (σ), while the pT-integrated ratios are compatible within 1σ. The observed trend is similar to that observed in the strange sector for the Λ/KS0 ratio. Model calculations including coalescence or statistical hadronization for charm-hadron formation are compared with the data.